2022
DOI: 10.26434/chemrxiv-2022-bx7cp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinetic traps in chemically fueled self-assembly and how to overcome them.

Abstract: Nature uses dynamic, molecular self-assembly to create cellular architectures that adapt to their environment. For example, a guanosine triphosphate (GTP)-driven reaction cycle activates and deactivates tubulin for assembly into microtubules and disassembly. Inspired by dynamic self-assembly in biology, multiple studies have developed synthetic analogs of assemblies regulated by chemical chemically fueled reaction cycles. A challenge in most of these studies is that molecules assemble upon activation but do no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…We hypothesize that either the product assembles and does not deactivate after assembly resulting in a static network, or, the product is deactivated in the fiber and does not disassemble before its reactivation in the fiber, which also results in a static fiber network. In line with previous work on similar peptides, 40,42 a 1 H-NMR-study showed that most of the peptides, be it in the precursor or product state, reside in the assembled state ( vide infra ). Thus, the precursor remains kinetically trapped within the fibers after deactivation and is reactivated before it can disassemble (Fig.…”
Section: Resultssupporting
confidence: 81%
“…We hypothesize that either the product assembles and does not deactivate after assembly resulting in a static network, or, the product is deactivated in the fiber and does not disassemble before its reactivation in the fiber, which also results in a static fiber network. In line with previous work on similar peptides, 40,42 a 1 H-NMR-study showed that most of the peptides, be it in the precursor or product state, reside in the assembled state ( vide infra ). Thus, the precursor remains kinetically trapped within the fibers after deactivation and is reactivated before it can disassemble (Fig.…”
Section: Resultssupporting
confidence: 81%
“…[23] However, we found that the EDC-triggered assemblies of DVV-4T are stable at room temperature (Figure S16), suggesting the influence of π-conjugated core on the stability of the assemblies formed upon the addition of EDC. In addition, the impeded disassembly process could be 10/21 attributed to the increased aspartic acid's apparent pKa after aggregate formation, [28,34,47] along with the impact of the hydrophobic π-conjugated motifs. [48] Considering that the peptidic monomers might form kinetically trapped assembly structures, we explored the effect of increasing the solution temperature to accelerate the hydrolysis of anhydride groups and the disassembly process.…”
Section: Thermally-assisted Disassembly Processmentioning
confidence: 99%
“…[85][86][87] As such, changing the pH of the pre-gelled solution can result in a change in the self-assembly due to differences in solubility. [88][89][90] Therefore, this is another potential way to tune the properties of the resulting hydrogels.…”
Section: Using Solution Phmentioning
confidence: 99%